O Espirita - dir. António Xavier Gorina (Pedro Lopes dos Santos)
Existências: A. 5, nº1 (out. 1924)- nº6 (mar. 1925) A. 5, nº 9 (jun. 1925)- nº10 (jul. 1925) A. 5, nº12 (set. 1925) A. 6, nº1 (jan. 1926)- nº8 (ago. 1926) Descrição baseada nos exemplares existentes na biblioteca